Qualities of effective teachers - Stronge, James H. (2002)
Este texto contiene temas como: What it means to be an effective teacher,prerequisites of effective teaching, the teacher as a person,classroom management and organization, teacher effectiveness:resources you can use, teacher skills assessment checklist
Keywords: Enseñanza de Maestros